(untitled) (Research, Society and Development, 2020)
This article deals with the report of an experiment carried out in three classes of the 9th grade of Elementary School, of a public school in the city of Rio de Janeiro. From the construction of pinhole camera by the students, we sought to associate the physical phenomenon with the teaching of mathematical concepts of homotetia and similarity of figures. After the stage of construction and observation, the students made reports to evaluate the activities. Throughout the experimental activity the participants presented different questions about the phenomenon observed, as well as perceived the correlation between similar figures and the concepts of geometric optics. Regarding student evaluation, in the reports they highlighted the importance of the proposed activity as a way to foster teamwork and the relevance of the practice to the teaching-learning process. Finally, it is noticed that the students’ interest in the activity, as well as the construction of the concept based on the questions, showed the importance of the strategy adopted for the teaching of Mathematics.